PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII6SMP NEGERI 20 PEKANBARU - Andita Septiastuti; Atma Murni; Jalinus ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to increase learning process and students’ mathachievement at class VIII6 SMPN 20 Pekanbaru through the implentation realisticmathematics education approach in cooperative learning model of STAD. The subjectwere 40 students from class VIII6 SMP Negeri 20 Pekanbaru consist of 17 male and 32female students with the heterogeneus level. This study used classroom action researchThe instruments of data collection in this research were observation sheets and studentsMathematic tests. The data which collected were analyzed with descriptive analyzedstatistically. From analyzed of teacher and students activity in the learning processshowed an improvement of learning process prior to the action on the first and secondcycle. The result of this research showed an increasing number of students’ mathachievement from the basic score 37.5% to 50% on the first daily test and 62.5% on thesecond daily test. Based on the result of this research can be concluded that theimplentation realistic mathematics education approach in cooperative learning modelof STAD can improve students’ math achievemsent at class VIII6 SMPN 20 Pekanbaruin the second semester academic years 2013/2014.Key Word : Students’ Math Achievement, Realistic Mathematics Education, CooperativeLearning Model of STAD, Classroom Action Research.